Molecular characterisation of ILRUN, a novel inhibitor of proinflammatory and antimicrobial cytokines. Issue 6 (June 2020) - Ambrose, Rebecca L.; Brice, Aaron M.; Caputo, Alessandro T.; Alexander, Marina R.; Tribolet, Leon; Liu, Yu Chih; Adams, Timothy E.; Bean, Andrew G.D.; Stewart, Cameron R.
Abstract: Regulation of type-I interferon (IFN) production is essential to the balance between antimicrobial defence and autoimmune disorders. The human protein-coding gene ILRUN (inflammation and lipid regulator with UBA-like and NBR1-like domains, previously C6orf106) was recently characterised as an inhibitor of antiviral and proinflammatory cytokine (interferon-alpha/beta and tumor necrosis factor alpha) transcription. Currently there is a paucity of information about the molecular characteristics of ILRUN, despite it being associated with several diseases including virus infection, coronary artery disease, obesity and cancer. Here, we characterise ILRUN as a highly phylogenetically conserved protein containing UBA-like and a NBR1-like domains that are both essential for inhibition of type-I interferon and tumor necrosis factor alpha) transcription in human cells. We also solved the crystal structure of the NBR1-like domain, providing insights into its potential role in ILRUN function. This study provides critical information for future investigations into the role of ILRUN in health and disease. Abstract : Immunolgy; Inflammation; Infectious disease; Immune Response; Viruses; Biochemistry; Biomolecules; ILRUN; C6orf106; innate immunity; interferon; p300; CBP